Comparative analysis of pregnancy and labour outcome among booked nullipara and primipara women in Sagamu, Nigeria - AO Sule-Odu (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
ackground: Pregnancy and childbirth are normal physiological processes. The best outcomes of most pregnancies are possible if adequate care is provided during pregnancy. Parity is one of the major determinants of pregnancy outcome. Objectives: To compare the pregnancy, labour and foetal outcomes of booked nulliparous and primiparous women. Methods: This is a retrospective, cross-sectional study conducted in the Department of Obstetrics and Gynaecology, Olabisi Onabanjo Teaching Hospital, Sagamu, Ogun State Nigeria from January 2014 to December 2016. Results: There was a significant difference between the mean age at booking of the nulliparous (Para 0) (26.7±4.4 years) and primiparous (Para 1) women (29.1±4.1 years) (p <0.001). The estimated gestational age (in weeks) at delivery was 38.1±4.8 in the Para 0 group and 38.2±3.9 in the Para 1 group. The mean duration of the first stage of labour was 11.3 ±5.7 hours in the Para 0 but 9.5 ± 5.3 hours in the Para 1 group and the difference was statistically significant (P<0.001). The maternal outcome was favourable in both groups of women even though two unavoidable deaths were recorded in the Para 1 group. The foetal outcomes in the two groups were comparable and both the Crude Odd Ratio and the Adjusted Odd Ratio differences in the two groups did not reach a significant level. Conclusion: Delivery outcomes in both groups were favourable and comparable. This can be attributed to the standard antenatal care received by both groups and well-supervised deliveries.